Risk assessment of psychiatric complications in infectious diseases: CALCulation of prognostic indices on example of COVID-19 - Sorokin, Mikhail; Markin, Kirill; Trufanov, Artem; Bocharova, Mariia; Tarumov, Dmitriy; Krasichkov, Alexander; Shichkina, Yulia; Medvedev, Dmitriy; Zubova, Elena (Frontiers in Psychiatry, 2024)
Methods A total of 177 individuals were examined, with 117 patients from a temporary infectious disease ward hospitalized due to COVID-19 forming the experimental group, and 60 patients from the outpatient department showing signs of acute respiratory viral infection comprising the validation group. The PLR index (platelet-to-lymphocyte ratio) and the CALC index (Comorbidity + Age + Lymphocyte + C-reactive protein) were calculated. Present state examination-10 (PSE-10), Hospital anxiety and depression scale (HADS), Montreal cognitive assessment (MoCA) were used to assess psychopathology in the sample. Regression and ROC-analysis, establishment of cut-off values for the COVID-19 prognosis indices, contingency tables, and comparison of means were used.The presence of multiple concurrent groups of psychopathological symptoms in the experimental group was associated (R²=0.28, F=5.63, p<0.001) with a decrease in the PLR index and a simultaneous increase in CALC. The AUC for the cut-off value of PLR was 0.384 (unsatisfactory). For CALC, the cut-off value associated with an increased risk of more psychopathological domains was 7 points (sensitivity=79.0%, specificity=69.4%, AUC=0.719). Those with CALC>7 were more likely to have disturbances in orientation (χ²=13.6; p<0.001), thinking (χ²=7.07; p= 0.008), planning ability (χ²=3.91; p= 0.048). In the validation group an association (R²McF=0.0775; p=0.041) between CALC values exceeding 7 points and the concurrent presence of pronounced anxiety, depression, and cognitive impairments was demonstrated (OR=1.52; p=0.038; AUC=0.66).In patients with COVID-19, the CALL index may be used for the risk-assessment of primary developed mental disturbances in the context of the underlying disease with a diagnostic threshold of 7 points.